PERANCANGAN SISTEM INFORMASI JASA SERVICE TELEVISI BERBASIS WEBSITE PADA GLOBAL ELEKTRONIK (KALI BARU) MENGGUNAKAN FRAMEWORK LARAVEL. - Muhammad Sadewo Wicaksono (2023)
The increasingly advanced development of information technology has now become an important element in all fields of activity. Therefore, entrepreneurs must be able to adapt to the rapid development of information technology so as not to be left behind compared to other competitors. Toko Global Electronics is a business that focuses on television repairs. Currently, this shop still relies on manual processes to manage goods data and service lists. As the number of customers increases, the complexity of managing goods data and service lists also increases. The aim is to design a system that can provide information regarding stock status and service lists more efficiently. In website development, researchers used the waterfall method for system design and the PIECES method for analyzing system requirements. The website coding process uses Visual Studio Code and the Laravel Framework and MySQL as the database. This research produces a website that can be used for managing goods data and service lists on Global Electronics. It is hoped that the creation of this application can be a solution to the problems experienced by Global Electronics.